Identifying locally advanced basal cell carcinoma eligible for treatment with vismodegib: an expert panel consensus. (February 2015) - Peris, Ketty; Licitra, Lisa; Ascierto, Paolo A; Corvò, Renzo; Simonacci, Marco; Picciotto, Franco; Gualdi, Giulio; Pellacani, Giovanni; Santoro, Armando
ABSTRACT : Basal cell carcinoma (BCC) is the most common skin cancer worldwide. Most occur on the head and neck, where cosmetic and functional outcomes are critical. BCC can be locally destructive if not diagnosed early and treated appropriately. Surgery is the treatment of choice for the majority of high-risk lesions. Aggressive, recurrent or unresectable tumors can be difficult to manage. Until recently, no approved systemic therapy was available for locally advanced or metastatic BCC inappropriate for surgery or radiotherapy. Vismodegib provides a systemic treatment option. However, a consensus definition of advanced BCC is lacking. A multidisciplinary panel with expertise in oncology, dermatology, dermatologic surgery and radiation oncology proposes a consensus definition based on published evidence and clinical experience.